Catalyst–solvent interactions in a dinuclear Ru-based water oxidation catalyst. Issue 47 (17th November 2016) - Shatskiy, Andrey; Lomoth, Reiner; Abdel-Magied, Ahmed F.; Rabten, Wangchuk; Laine, Tanja M.; Chen, Hong; Sun, Junliang; Andersson, Pher G.; Kärkäs, Markus D.; Johnston, Eric V.; Åkermark, Björn
Abstract : A new dinuclear ruthenium-based water oxidation catalyst is described. Insight is provided into interactions between the catalyst and acetonitrile, a common co-solvent in water oxidation catalysis. Abstract : Photocatalytic water oxidation represents a key process in conversion of solar energy into fuels and can be facilitated by the use of molecular transition metal-based catalysts. A novel straightforward approach for covalent linking of the catalytic units to other moieties is demonstrated by preparation of a dinuclear complex containing two [Ru(pdc)(pic)3 ]-derived units (pdc = 2, 6-pyridinedicarboxylate, pic = 4-picoline). The activity of this complex towards chemical and photochemical oxidation of water was evaluated and a detailed insight is given into the interactions between the catalyst and acetonitrile, a common co-solvent employed to increase solubility of water oxidation catalysts. The solvent-induced transformations were studied by electrochemical and spectroscopic techniques and the relevant quantitative parameters were extracted.